Self-determination for all language learners: New applications for formal language education. (November 2019) - McEown, Maya Sugita; Oga-Baldwin, W.L. Quint
Abstract: Self-determination theory (SDT; Deci & Ryan, 1985) is an established macro-theory of human motivation, and differentiates two broad motivational orientations: intrinsic and extrinsic motivation. SDT is comprised of 6 mini-theories, each designed to address questions about human motivation and the process that facilitate and harm it. For foreign language researchers, these theories offer a clear, integrated framework for understanding motivation that translates across disciplines. For language teachers, SDT offer integrated principles for how to improve motivational quality. For language learners in formal education settings, these mini-theories offer a comprehensive set of ideas for generating internally regulated motives. This article will provide a comprehensive, up-to-date overview of SDT and how it can be applied to relevant issues in language education research and pedagogy.